2017
DOI: 10.3233/cbm-160676
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of serum microRNAs miR-21 and miR-106a in renal cell carcinoma

Abstract: We conclude that serum miR-21 and miR106a are expected to be molecular markers for RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…Emerging evidence suggests that miRNAs are involved in tumor development and progression (19). In the present study, miR-136-5p was revealed to be downregulated in RCC tissues and cell lines compared with adjacent non-tumor tissues and cells in vitro.…”
Section: Discussionsupporting
confidence: 48%
“…Emerging evidence suggests that miRNAs are involved in tumor development and progression (19). In the present study, miR-136-5p was revealed to be downregulated in RCC tissues and cell lines compared with adjacent non-tumor tissues and cells in vitro.…”
Section: Discussionsupporting
confidence: 48%
“…Transwell chamber inserts (BD Biosciences, Franklin Lakes, NJ, USA) with (for invasion) or without Matrigel (for migration) were used in the assay according to the manufacturer's protocol. Briefly, 200 µl serum-free medium containing ~1x10 4 transfected cells was plated in the upper compartment of the chamber. Complete medium as the source of chemo-attractants was added into the lower chamber.…”
Section: Micrornamentioning
confidence: 99%
“…Clear cell RCC is the most common subtype accounting for approximately 75% of all RCC cases (2). According to the American Joint Committee on Cancer staging of RCC (3), the 5-year survival rate of patients with stage I RCC is ~98%, while that of patients with stage III is ~5% (4). Thus, early detection and treatment is important.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miR-106 has been studied in renal cell carcinoma (RCC) [18], osteosarcoma [19], and gastric [20], lung [21], and colorectal [22] cancers. Moreover, the diagnostic and prognostic significance of miR-106 has also been explored in several cancer types.…”
Section: Introductionmentioning
confidence: 99%